Effect of Family Setup on Interpersonal Relationship in Married People: A Comparative Study - Nusrat Jabeen ,; Dr Aliya Ali,; Mahvish Noorian,; Muneeza Tasleem,; Ibarat Ali Laghari,; Meer Arsalan khan, (Dialogue Social Science Review (DSSR), 2025)
This research investigates what role family structure plays in shaping attachment styles among married people residing in Karachi, Pakistan, between nuclear and joint family environments. Research investigates how South Asian family structures impact three types of attachment patterns during marital relationships since family environments carry great social importance in South Asian cultures. This study involved 100 married adults, dividing them into two groups: fifty nuclear families and fifty joint families. We acquired the research data by administering the Revised Adult Attachment Scale (RAAS) – Close Relationships Version (Collins, 1996). The independent samples t-test operation evaluated scores for attachment between both participant groups. Nuclear family members identified significantly stronger close attachment feelings and dependency toward their spouses, which indicated more emotional closeness and reliance. The research showed that participants from joint families scored higher on anxious attachment scores, which implies both emotional insecurity and relationship anxiety. The study backs earlier research conducted by Ayub and Iqbal (2012) and Khan and Aftab (2019) because it proves how privacy and autonomy, together with spousal interaction, help form secure attachment. The research results confirm Qadir and his colleagues' (2013) conclusion that external family involvement in traditional joint households leads to relationship anxiety. According to the study results, nuclear families maintain superior conditions for marital bond security, but joint families enable access to social support, which also produces emotional stress from family interference. Marriage counselors and psychologists, together with policymakers, should take note of the research findings because they demonstrate how family structures affect the psychological aspects of marital happiness. Future studies need to examine how family environments affect relationships in South Asian marriages across time as well as study other sociocultural plus economic elements that affect these bonds.